Fabrication of polysulfone/chitosan composite membrane with various concentrations of polysulfone / Norin Zamiah Kassim Shaari, Mohammad Najib Mohmad Ishak and Nurul Aida Sulaiman - Kassim Shaari, Norin Zamiah; Mohmad Ishak, Mohammad Najib; Sulaiman, Nurul Aida (Universiti Teknologi MARA Shah Alam, 2019)
In this study, a thin film composite (TFC) membrane was fabricated by using polysulfone (PSF) membrane as a supporting layer and hybrid membrane as a barrier layer. The PSF membranes were prepared by using phase inversion method while the hybrid membranes were formulated from polymer blend of chitosan (CS)/polyethylene glycol (PEG) and cross linked with tetraethylorthosilicate (TEOS). The aim of this work is to study the effects of varying the PSF concentrations on the characterisation and performance of the TFC membranes. Three different PSF concentrations were selected; 11 wt.%, 13 wt.%, and 15 wt.%. The TFC membrane was characterised by using attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy and thermogravimetric analysis (TGA). In the performance testing, pure water permeability (PWP) was conducted to measure water flux, and antifouling experiment by using humic acid and deionised water as feed solution was carried out. Results show that TFC membrane with 11 wt.% PSF has excellent membrane characteristics and performance. This membrane shows better water permeation, and has antifouling properties, which was exhibited through high relative flux recovery (RFR) and low relative flux decay (RFD) as compared to other membranes. This fabricated membrane has potential to be used in wastewater treatment highlight the most significant findings or observations that would attract attention of readers.